Greenpeace Indonesia Analysis as Pressure Group In Controlling Environmental Policy In Anies Baswedan Government (Study On The Role Of Greenpeace Indonesia On Policy Emphasis For Efforts To Improve Clean Air Quality DKI Jakarta) - Resky Ramadhona; Wiwi Widiastuti; Fotriyani Yuliawati (International Journal of Social Sciences Review, 2021)
This research aims to find out the role of Greenpeace Indonesia as a pressure group on air pollution and related to the Jakarta government policy. In addition, this study also describes the State ignoring environmental damage that triggers the birth of NGO intermediary actors who care about environmental sustainability. Through his campaign action efforts to suppress and demand policies issued. This research uses civil society theory, intermediary actors, and the definition of the pressure group itself. The method used is a qualitative method with descriptive-analytical in controlling environmental policy by using a case study approach to reduce the clean air quality DKI Jakarta. Data collection techniques are obtained through in-depth interviews, observations, and documentation that further use data analysis techniques to be analyzed from the data that has been obtained. Then the validity of the data used by researchers is the triangulation of sources to double-check the data so that the data obtained is reliable.